A Field Study on Food Communities in the Context of Ecological Habitus - Gamze Gürler; Birtan Bozlu (Journal of Economy Culture and Society)
This research reveals the relationship between social actors’ cultural capital, ecological predispositions, and food consumption practices.To achieve this, a qualitative analysis was carried out on the Antalya Food Community. Alternative food communities, which are part of ecological movements, address collective demands and social problems related to the production, distribution, and consumption of food. Participation in these communities requires certain kinds of cultural capital. Food consumption strategies are closely related to ecological habitus. Ecological habitus is a concept that points to the practice of how to live better in a particular place; the concept was developed under the influence of Bourdieu (1998). Alternative food communities are said to attract middleclass individuals who have a common ecological habitus. Information from in-depth interviews and participant observations are used to explain the main motivations of the members, the ecological habitus that makes the community possible, the relation networks they produce, and the various strategies and practices developed by these members. The fact that individuals develop ecological interests besides food after joining the community shows that these communities can be seen as “learning places” (Haluza-Delay, 2008). Thus, alternative food communities go beyond being a place for food exchange due to their ecological activities.